Flexible conductive film and preparation method and application thereof

By preparing a flexible conductive film containing PEDOT: PSS, water-soluble polymer, viscous additive, humectant and polar solvent, the problems of weakening tensile properties of conductive films and lack of adhesion in the prior art are solved, and a conductive film with high stability, flexibility and adhesion is achieved, which is suitable for long-range monitoring of electrophysiological signals.

CN119626633APending Publication Date: 2025-03-14CAPITALBIO CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411852898.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

After being stored for a period of time, the tensile performance of the existing flexible conductive film gradually weakens, making it difficult to maintain the stability of the conductive film, and at the same time lacks adhesion and cannot fit closely with the skin.

Method used

By drying the solution of PEDOT:PSS, water-soluble polymer, viscous additive, moisturizer and polar solvent, a flexible conductive film with good flexibility, stretchability and adhesion was prepared.

Benefits of technology

The long-term stability of the conductive film is achieved, good flexibility and stretchability are maintained, and the adhesion to the skin is enhanced, which is suitable for long-range monitoring of electrophysiological signals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191039650000141
    Figure BDA0005191039650000141
  • Figure BDA0005191039650000151
    Figure BDA0005191039650000151
  • Figure BDA0005191039650000161
    Figure BDA0005191039650000161
Patent Text Reader

Abstract

The invention relates to the technical field of flexible electronics, in particular to a flexible conductive film and a preparation method and application thereof. The flexible conductive film is obtained by drying a solution containing PEDOT: PSS, a water-soluble polymer, a viscous auxiliary agent, a humectant and a polar solvent, in the solution, the mass content of the PEDOT: PSS is 0.1%-1%, the mass content of the water-soluble polymer is 0.2%-3%, the mass content of the viscous additive is 0.5%-10%, the mass content of the humectant is 1%-10%, and the mass content of the polar solvent is 1%-8%. The flexible conductive thin film provided by the invention has relatively good flexibility, stretchability and adhesion, also shows excellent properties such as good biocompatibility and motion interference resistance, and is suitable for long-range monitoring of electrophysiological signals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible electronic technology, and in particular to a flexible conductive film, a preparation method and application thereof. Background Art

[0002] With the development of miniaturization, flexibility and multifunctionality of electronic devices, flexible conductive materials have become a hot topic for domestic and foreign scholars. Flexible conductive materials are flexible and conductive, and are widely used in health management materials, sensors, wearable devices and other fields. Among them, in the field of medical diagnosis and treatment, flexible conductive materials can be used to detect human blood pressure, electrocardiogram, electromyography, electroencephalogram, breathing, swallowing function, etc., and the electrophysiological indicators obtained can provide corresponding health information. Electrophysiology includes the recording of electrical signals or methods of influencing signals by using electrodes as stimuli to transfer electric charges. Electrodes as interfaces between people and devices are crucial to both of the above technologies. In view of the need for electrophysiological information and device comfort, such electrodes are required to have high signal quality while also having good flexibility, stretchability and reliable adhesion, so as to fit closely with the skin.

[0003] At present, most electrophysiological electrodes use gel electrodes, which are large in size and lack flexibility. The conductive gel has a high water content and is easy to dry and harden, lose conductivity, and cause monitoring failure. Several popular materials such as carbon nanotubes, metal nanowires, graphene and conductive polymers have been widely studied as possible alternatives to flexible electrodes. Among them, the conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) has good biocompatibility, high conductivity and high electrochemical stability, and has high transmittance in the visible light region, becoming a new generation of flexible conductive electrodes. However, pure PEDOT:PSS film has a strain of no more than 5%, which is not enough for most skin deformations. Therefore, it is necessary to further study the means of PEDOT:PSS structural regulation to obtain a structure that is more conducive to performance and develop PEDOT:PSS films with better performance, which has important guiding significance for the further application of PEDOT:PSS stretchable electrodes. By taking advantage of the good solution processing properties of PEDOT:PSS and flexibly adjusting its molecular structure, mechanical properties and electrical properties, it is possible to provide specific functions according to application scenarios, providing additional advantages for multiple scenarios of flexible electronic products.

[0004] In the related technical solutions, PEDOT:PSS is generally toughened by adding a flexible polymer. Although the tensile properties of the conductive film can be improved, the tensile properties will gradually weaken after a period of conventional storage, and finally return to a low elongation at break state, making it difficult to maintain the stability of the conductive film. Therefore, it is urgent to provide a conductive polymer suitable for PEDOT:PSS, which can be used to prepare a conductive film with good flexibility, good adhesion and high stability.

[0005] Patent application CN115785499A provides a highly conductive stretchable PEDOT:PSS film and its preparation method and application. The PEDOT:PSS film is composed of a conductive polymer PEDOT:PSS and a water-soluble polymer polyvinyl alcohol and a polyhydroxy compound sorbitol or glycerol as a dopant. However, the disadvantage of this technology is that the conductive film has no adhesion and cannot fit closely to the skin.

[0006] Patent application CN116612932A provides a patternable flexible electrode film and its preparation method and application, by preparing a solution containing polar solvent, PEDOT:PSS, PVA, viscosity aid, thickener and surfactant, and drying, to obtain the flexible electrode film. However, the performance stability of the flexible electrode film is poor, and it will lose its original flexibility, stretchability and adhesion after being placed for a period of time. Moreover, the added surfactant has a certain degree of toxicity risk, which may affect the environment and health. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a flexible conductive film, a preparation method and application thereof. The flexible conductive film provided by the present invention has good flexibility, stretchability and adhesion, and at the same time exhibits excellent properties such as good biocompatibility and resistance to motion interference, and is suitable for long-term monitoring of electrophysiological signals.

[0008] The present invention provides a flexible conductive film, which is obtained by drying a solution containing PEDOT:PSS, a water-soluble polymer, a viscosity aid, a moisturizing agent and a polar solvent;

[0009] In the solution, the mass content of PEDOT:PSS is 0.1% to 1%, the mass content of water-soluble polymer is 0.2% to 3%, the mass content of viscosity auxiliary agent is 0.5% to 10%, the mass content of moisturizing agent is 1% to 10%, and the mass content of polar solvent is 1% to 8%.

[0010] Preferably, the water-soluble polymer includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylamide and polyethylene glycol; the viscosity auxiliary agent includes at least one of tannic acid, dopamine, tea polyphenols, catechins, anthocyanins and proanthocyanidins; the moisturizer includes at least one of glycerin, propylene glycol, butylene glycol, hyaluronic acid, trehalose, squalane, hyaluronic acid, octadecyl alcohol, sorbitol, urea and D-panthenol; the polar solvent includes at least one of ethylene glycol and dimethyl sulfoxide.

[0011] Preferably, the thickness of the flexible conductive film is 20-200 μm.

[0012] The present invention also provides a method for preparing the above-mentioned flexible conductive film, comprising the following steps:

[0013] A PEDOT:PSS aqueous solution, a water-soluble polymer, a viscosity aid, a humectant, a polar solvent and water are mixed, and the obtained solution is dried to obtain a flexible conductive film.

[0014] Preferably, the method for preparing the flexible conductive film comprises the following steps:

[0015] S1) stirring and mixing solution A, solution B, solution C and a moisturizer to obtain solution D;

[0016] The solution A is obtained by mixing a PEDOT:PSS aqueous solution and a polar solvent;

[0017] The solution B is obtained by dissolving a water-soluble polymer in water;

[0018] The solution C is obtained by dissolving a viscosity aid in water;

[0019] S2) adding the solution D dropwise onto the substrate, and after drying, obtaining a flexible conductive film.

[0020] Preferably, the mixing of the PEDOT:PSS aqueous solution and the polar solvent is carried out at room temperature; the mixing is carried out by stirring.

[0021] Preferably, the solution B is obtained by mixing a water-soluble polymer and water, and heating and stirring until the water-soluble polymer is completely dissolved in water; the heating and stirring temperature is 75-85° C.; and the mass concentration of the solution B is 2.2%-10%.

[0022] Preferably, the solution C is obtained by mixing a viscosity aid and water, and stirring until the viscosity aid is completely dissolved in the water; the stirring temperature is room temperature; and the mass concentration of the solution C is 2% to 16.7%.

[0023] The present invention also provides an application of the flexible conductive film described above, or the flexible conductive film prepared by the preparation method described above, in a flexible electronic device.

[0024] The present invention also provides a flexible electronic device, comprising the flexible conductive film described above, or the flexible conductive film prepared by the preparation method described above.

[0025] In the present invention, polyvinyl alcohol is a soft polymer that can improve the elongation at break of PEDOT:PSS and can effectively increase the tensile properties of the film. However, due to the insulating properties of polyvinyl alcohol, the conductivity of the film decreases as the amount of polyvinyl alcohol added increases. Ethylene glycol is a polar solvent containing hydroxyl groups. The addition of ethylene glycol can induce secondary doping of PEDOT:PSS, causing phase separation between the PEDOT region and the PSS region, thereby causing the PEDOT region to aggregate and produce a better conductive path to improve the conductivity of the film. The phenolic hydroxyl structure contained in tannic acid has a strong physical force on the substrate and is an adhesive; tannic acid can serve as a cross-linking point between polyvinyl alcohol chains to form a supramolecular complex with viscosity and elasticity, and form a strong adhesion with the substrate through van der Waals force and mechanical interlocking. Adding an appropriate amount of tannic acid can make the flexible conductive film have a lower Young's modulus, thereby having better adhesion, compliance and stretchability, which is crucial for conformal adhesion between the electrode and the skin. The humectant, including at least one of glycerol and propylene glycol, has strong water absorption, and its molecular structure has polarity, so that it can strongly interact with water molecules and absorb moisture in the air. The humectant can form hydrogen bonds with water and polyvinyl alcohol molecules, and has excellent water retention performance. The conductive film is placed in a dry environment for more than 28 days and still has good flexibility and stretchability, which is also beneficial to the storage of the conductive film or the use in extreme cases. At the same time, polyvinyl alcohol contains hydroxyl groups, and the humectant can also be used as a plasticizer for polyvinyl alcohol, so the mechanical tensile properties of the film can be further improved. The above-mentioned components can cooperate well with each other, and the flexible conductive film finally obtained has good flexibility, stretchability, and adhesion, and shows excellent properties such as good biocompatibility and anti-motion interference, and is suitable for long-term monitoring of electrophysiological signals. In addition, the flexible conductive film provided by the present invention still has good flexibility and stretchability after being placed in a dry environment for a period of time, which is very beneficial to the storage of the conductive film or the use in extreme cases. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a graph showing the test results of myoelectric signal conduction performance of the PEDOT:PSS flexible conductive films prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 7 as flexible electrodes. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention provides a flexible conductive film, which is obtained by drying a solution containing PEDOT:PSS, a water-soluble polymer, a viscosity aid, a moisturizing agent and a polar solvent;

[0029] In the solution, the mass content of PEDOT:PSS is 0.1% to 1%, the mass content of water-soluble polymer is 0.2% to 3%, the mass content of viscosity auxiliary agent is 0.5% to 10%, the mass content of moisturizing agent is 1% to 10%, and the mass content of polar solvent is 1% to 8%.

[0030] Specifically, in the solution, the mass content of PEDOT:PSS is 0.2%, 0.33%, 0.34%, 0.35%, and 1%.

[0031] In the solution, the mass content of the water-soluble polymer is 0.33%, 0.64%, 0.65%, 0.66%, 0.67% and 3%.

[0032] In the solution, the mass content of the viscosity aid is 0.92%, 1.7%, 3.4%, 4.5%, 5.6% and 10%.

[0033] In the solution, the mass content of the moisturizer is preferably 2% to 7%, such as 2.5%, 4.8%, or 6.9%.

[0034] In the solution, the mass content of the polar solvent is 1%, 5.6%, 5.7% and 5.8%.

[0035] In some embodiments of the present invention, the flexible conductive film is obtained by drying a solution of a mixture of PEDOT:PSS, a water-soluble polymer, a viscosity aid, a moisturizing agent, a polar solvent and water, and the water is deionized water.

[0036] In certain embodiments of the present invention, the water-soluble polymer is at least one of polyvinyl alcohol (PVA), polyvinyl pyrrolidone, polyacrylamide and polyethylene glycol; the viscosity aid is at least one of tannic acid, dopamine, tea polyphenols, catechins, anthocyanins and proanthocyanidins; the moisturizer is at least one of glycerin, propylene glycol, butylene glycol, hyaluronic acid, trehalose, squalane, hyaluronic acid, octadecyl alcohol, sorbitol, urea and D-panthenol; the polar solvent is at least one of ethylene glycol and dimethyl sulfoxide.

[0037] In some embodiments of the present invention, the thickness of the flexible conductive film is 20-200 μm, such as 50-130 μm, specifically 66 μm, 115 μm, 65 μm, 113 μm, 61 μm, 108 μm, 127 μm, 63 μm, 107 μm, 57 μm, or 106 μm.

[0038] The flexible conductive film provided by the present invention does not contain surfactants and thickeners.

[0039] The present invention also provides a method for preparing the above-mentioned flexible conductive film, comprising the following steps:

[0040] The PEDOT:PSS aqueous solution, water-soluble polymer, viscosity aid, moisturizing agent, polar solvent and water are mixed, and the obtained solution is dried to obtain a flexible conductive film. The water is deionized water.

[0041] Specifically, the method for preparing the flexible conductive film comprises the following steps:

[0042] S1) stirring and mixing solution A, solution B, solution C and a moisturizer to obtain solution D;

[0043] The solution A is obtained by mixing a PEDOT:PSS aqueous solution and a polar solvent;

[0044] The solution B is obtained by dissolving a water-soluble polymer in water;

[0045] The solution C is obtained by dissolving a viscosity aid in water;

[0046] S2) adding the solution D dropwise onto the substrate, and after drying, obtaining a flexible conductive film.

[0047] In step S1):

[0048] In certain embodiments of the present invention, the PEDOT:PSS aqueous solution is commonly available on the market, such as Clevios PH1000, with a solid content of 1.0% to 1.3%, wherein the mass ratio of PEDOT to PSS is 1:2.5.

[0049] In certain embodiments of the present invention, the mixing of the PEDOT:PSS aqueous solution and the polar solvent is performed at room temperature. The mixing is performed by stirring and mixing for 0.3 to 0.7 hours, such as 0.5 hours.

[0050] In certain embodiments of the present invention, the solution B is obtained by mixing a water-soluble polymer and water, and then heating and stirring until the water-soluble polymer is completely dissolved in the water. The water is deionized water. The temperature of the heating and stirring is 75 to 85° C., such as 80° C.; the time is 0.8 to 1.2 hours, such as 1 hour. The mass concentration of the solution B is 2.2% to 10%, such as 2.2%, 10%.

[0051] In certain embodiments of the present invention, the solution C is obtained by mixing a viscosity aid and water, and stirring until the viscosity aid is completely dissolved in the water. The water is deionized water. The stirring temperature is room temperature, and the stirring time is 0.3 to 0.7 hours, such as 0.5 hours. The mass concentration of the solution C is 2% to 16.7%, such as 5.7%, 10.7%, 13.8%, 16.7%.

[0052] In certain embodiments of the present invention, the temperature for stirring and mixing the solution A, solution B, solution C and the moisturizing agent is room temperature and the time is 0.8 to 1.2 hours, such as 1 hour.

[0053] In step S2):

[0054] In certain embodiments of the present invention, the solution D is dripped onto the substrate using a pipette.

[0055] The substrate is a glass sheet.

[0056] In certain embodiments of the present invention, the drying temperature is 40-100° C. and the drying time is not less than 1 hour.

[0057] In certain embodiments of the present invention, after the drying, the method further comprises: naturally cooling to room temperature and then peeling off.

[0058] The present invention also provides an application of the flexible conductive film described above, or the flexible conductive film prepared by the preparation method described above, in a flexible electronic device. Specifically, the flexible conductive film, or the flexible conductive film prepared by the preparation method described above, is used as a flexible electrode in a flexible electronic device.

[0059] The present invention also provides a flexible electronic device, comprising the flexible conductive film described above, or the flexible conductive film prepared by the preparation method described above. The flexible conductive film, or the flexible conductive film prepared by the preparation method described above, is used as a flexible electrode.

[0060] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0061] In order to further illustrate the present invention, a flexible conductive film, a preparation method and applications thereof provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0062] Example 1

[0063] Preparation of flexible conductive film:

[0064] (1) Add 2 g of ethylene glycol to 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000), and stir at room temperature for 0.5 h to mix evenly to obtain solution A;

[0065] (2) polyvinyl alcohol and deionized water were mixed, and heated and stirred at 80° C. for 1 h to completely dissolve the polyvinyl alcohol in the deionized water to obtain solution B (polyvinyl alcohol solution) with a mass concentration of 2.2%;

[0066] (3) Mix tannic acid and deionized water, and stir at room temperature for 0.5 h to completely dissolve tannic acid in deionized water to obtain solution C (tannic acid solution) with a mass concentration of 5.7%;

[0067] (4) adding 10.2 g of solution B (polyvinyl alcohol solution), 10.6 g of solution C (tannic acid solution), and 1.6 g of glycerol to solution A in step (1), stirring at room temperature for 1 h, to obtain solution D;

[0068] In the solution D, the mass content of PEDOT:PSS is 0.35%, the mass content of the water-soluble polymer (polyvinyl alcohol) is 0.67%, the mass content of the viscosity aid (tannic acid) is 1.7%, the mass content of the humectant (glycerol) is 4.8%, and the mass content of the polar solvent (ethylene glycol) is 5.8%;

[0069] (5) Use a pipette to take a proper amount of solution D and drop it on a glass substrate, and dry it at 60°C for 1 hour to obtain a PEDOT:PSS flexible conductive film with a thickness of 66 μm. The electrical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0070] (6) Use a pipette to take another portion of solution D and drop it on a disposable culture dish, dry it at 60°C for 10 hours, cool it, and peel it off to obtain a PEDOT:PSS flexible conductive film with a film thickness of 115 μm. The mechanical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0071] Example 2

[0072] Preparation of flexible conductive film:

[0073] (1) Add 2 g of ethylene glycol to 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000), and stir at room temperature for 0.5 h to mix evenly to obtain solution A;

[0074] (2) polyvinyl alcohol and deionized water were mixed, and heated and stirred at 80° C. for 1 h to completely dissolve the polyvinyl alcohol in the deionized water to obtain solution B (polyvinyl alcohol solution) with a mass concentration of 2.2%;

[0075] (3) Tannic acid and deionized water were mixed and stirred at room temperature for 0.5 h to completely dissolve the tannic acid in the deionized water to obtain solution C (tannic acid solution) with a mass concentration of 10.7%;

[0076] (4) adding 10.2 g of solution B (polyvinyl alcohol solution), 11.2 g of solution C (tannic acid solution), and 1.7 g of glycerol to solution A in step (1), and stirring at room temperature for 1 h to obtain solution D;

[0077] In the solution D, the mass content of PEDOT:PSS is 0.34%, the mass content of the water-soluble polymer (polyvinyl alcohol) is 0.66%, the mass content of the viscosity aid (tannic acid) is 3.4%, the mass content of the humectant (glycerol) is 4.8%, and the mass content of the polar solvent (ethylene glycol) is 5.7%;

[0078] (5) Use a pipette to take a proper amount of solution D and drop it on a glass substrate, and dry it at 60°C for 1 hour to obtain a PEDOT:PSS flexible conductive film with a thickness of 65 μm. The electrical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0079] (6) Use a pipette to take another portion of solution D and drop it on a disposable culture dish, dry it at 60°C for 10 hours, cool it, and peel it off to obtain a PEDOT:PSS flexible conductive film with a film thickness of 113 μm. The mechanical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0080] Example 3

[0081] Preparation of flexible conductive film:

[0082] (1) Add 2 g of ethylene glycol to 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000), and stir at room temperature for 0.5 h to mix evenly to obtain solution A;

[0083] (2) polyvinyl alcohol and deionized water were mixed, and heated and stirred at 80° C. for 1 h to completely dissolve the polyvinyl alcohol in the deionized water to obtain solution B (polyvinyl alcohol solution) with a mass concentration of 2.2%;

[0084] (3) Mix tannic acid and deionized water, and stir at room temperature for 0.5 h to completely dissolve tannic acid in deionized water to obtain solution C (tannic acid solution) with a mass concentration of 13.8%;

[0085] (4) adding 10.2 g of solution B (polyvinyl alcohol solution), 11.6 g of solution C (tannic acid solution), and 1.7 g of glycerol to solution A in step (1), stirring at room temperature for 1 h, to obtain solution D;

[0086] In the solution D, the mass content of PEDOT:PSS is 0.34%, the mass content of the water-soluble polymer (polyvinyl alcohol) is 0.65%, the mass content of the viscosity aid (tannic acid) is 4.5%, the mass content of the humectant (glycerol) is 4.8%, and the mass content of the polar solvent (ethylene glycol) is 5.6%;

[0087] (5) Use a pipette to take a proper amount of solution D and drop it on a glass substrate, and dry it at 60°C for 1 hour to obtain a PEDOT:PSS flexible conductive film with a thickness of 61 μm. The electrical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0088] (6) Use a pipette to take another portion of solution D and drop it on a disposable culture dish, dry it at 60°C for 10 hours, cool it, and peel it off to obtain a PEDOT:PSS flexible conductive film with a film thickness of 108 μm. The mechanical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0089] Example 4

[0090] Preparation of flexible conductive film:

[0091] (1) Add 0.12 g of ethylene glycol to 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000), and stir at room temperature for 0.5 h to mix well to obtain solution A;

[0092] (2) mixing polyvinyl alcohol and deionized water, heating and stirring at 80° C. for 1 h to completely dissolve the polyvinyl alcohol in the deionized water, to obtain solution B (polyvinyl alcohol solution) with a mass concentration of 10%;

[0093] (3) Mix tannic acid and deionized water, and stir at room temperature for 0.5 h to completely dissolve tannic acid in deionized water to obtain solution C (tannic acid solution) with a mass concentration of 16.7%;

[0094] (4) adding 0.39 g of solution B (polyvinyl alcohol solution), 0.66 g of solution C (tannic acid solution), and 0.83 g of glycerol to solution A in step (1), and stirring at room temperature for 1 h to obtain solution D;

[0095] In the solution D, the mass content of PEDOT:PSS is 1%, the mass content of the water-soluble polymer (polyvinyl alcohol) is 0.33%, the mass content of the viscosity aid (tannic acid) is 0.92%, the mass content of the humectant (glycerol) is 6.9%, and the mass content of the polar solvent (ethylene glycol) is 1%;

[0096] (5) Use a pipette to take a proper amount of solution D and drop it on a glass substrate, and dry it at 60°C for 1 hour to obtain a PEDOT:PSS flexible conductive film with a thickness of 66 μm. The electrical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0097] (6) Use a pipette to take another portion of solution D and drop it on a disposable culture dish, dry it at 60°C for 10 hours, cool it, and peel it off to obtain a PEDOT:PSS flexible conductive film with a film thickness of 127 μm. The mechanical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0098] Example 5

[0099] Preparation of flexible conductive film:

[0100] (1) Add 0.6 g of ethylene glycol to 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000), and stir at room temperature for 0.5 h to mix well to obtain solution A;

[0101] (2) mixing polyvinyl alcohol and deionized water, heating and stirring at 80° C. for 1 h to completely dissolve the polyvinyl alcohol in the deionized water, to obtain solution B (polyvinyl alcohol solution) with a mass concentration of 10%;

[0102] (3) Mix tannic acid and deionized water, and stir at room temperature for 0.5 h to completely dissolve tannic acid in deionized water to obtain solution C (tannic acid solution) with a mass concentration of 16.7%;

[0103] (4) adding 12 g of solution B (polyvinyl alcohol solution), 35.9 g of solution C (tannic acid solution), and 1.5 g of glycerol to solution A in step (1), stirring at room temperature for 1 h, to obtain solution D;

[0104] In the solution D, the mass content of PEDOT:PSS is 0.2%, the mass content of the water-soluble polymer (polyvinyl alcohol) is 3%, the mass content of the viscosity aid (tannic acid) is 10%, the mass content of the humectant (glycerol) is 2.5%, and the mass content of the polar solvent (ethylene glycol) is 1%;

[0105] (5) Use a pipette to take a proper amount of solution D and drop it on a glass substrate, and dry it at 60°C for 1 hour to obtain a PEDOT:PSS flexible conductive film with a thickness of 63 μm. The electrical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0106] (6) Use a pipette to take another portion of solution D and drop it on a disposable culture dish, dry it at 60°C for 10 hours, cool it, and peel it off to obtain a PEDOT:PSS flexible conductive film with a thickness of 107 μm. The mechanical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0107] Example 6

[0108] Preparation of flexible conductive film:

[0109] (1) Add 2 g of ethylene glycol to 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000), and stir at room temperature for 0.5 h to mix evenly to obtain solution A;

[0110] (2) mixing polyvinyl pyrrolidone and deionized water, and stirring for 1 h to completely dissolve the polyvinyl pyrrolidone in the deionized water to obtain solution B (polyvinyl pyrrolidone solution) with a mass concentration of 2.2%;

[0111] (3) Mix tannic acid and deionized water, and stir at room temperature for 0.5 h to completely dissolve tannic acid in deionized water to obtain solution C (tannic acid solution) with a mass concentration of 16.7%;

[0112] (4) adding 10.2 g of solution B (polyvinyl pyrrolidone solution), 12 g of solution C (tannic acid solution), and 1.7 g of glycerol to solution A in step (1), stirring at room temperature for 1 h, to obtain solution D;

[0113] In the solution D, the mass content of PEDOT:PSS is 0.33%, the mass content of the water-soluble polymer (polyvinyl pyrrolidone) is 0.64%, the mass content of the viscosity aid (tannic acid) is 5.6%, the mass content of the humectant (glycerol) is 4.8%, and the mass content of the polar solvent (ethylene glycol) is 5.6%;

[0114] (5) Use a pipette to take a proper amount of solution D and drop it on a glass substrate, and dry it at 60°C for 1 hour to obtain a PEDOT:PSS flexible conductive film with a thickness of 57 μm. The electrical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0115] (6) Use a pipette to take another portion of solution D and drop it on a disposable culture dish, dry it at 60°C for 8 hours, cool it, and peel it off to obtain a PEDOT:PSS flexible conductive film with a film thickness of 106 μm. The mechanical properties of the prepared PEDOT:PSS flexible conductive film were tested and verified, and the results are shown in Table 1.

[0116] Example 7

[0117] The difference from Example 2 is:

[0118] In step (2):

[0119] (2) Mixing polyethylene glycol and deionized water, stirring for 1 h to completely dissolve the polyethylene glycol in the deionized water, to obtain solution B (polyethylene glycol solution) with a mass concentration of 2.2%;

[0120] The remaining steps are the same as those in Example 2 to obtain a PEDOT:PSS flexible conductive film.

[0121] Example 8

[0122] The difference from Example 2 is:

[0123] Replace tannic acid with dopamine.

[0124] Example 9

[0125] The difference from Example 2 is:

[0126] Replace tannic acid with tea polyphenols.

[0127] Example 10

[0128] The difference from Example 2 is:

[0129] Replace tannic acid with anthocyanins.

[0130] Embodiment 11

[0131] The difference from Example 2 is:

[0132] Replace glycerin with propylene glycol.

[0133] Example 12

[0134] The difference from Example 2 is:

[0135] Replace glycerin with squalane.

[0136] Embodiment 13

[0137] The difference from Example 2 is:

[0138] Replace glycerin with hyaluronic acid.

[0139] Embodiment 14

[0140] The difference from Example 2 is:

[0141] Replace ethylene glycol with dimethyl sulfoxide.

[0142] Comparative Example 1

[0143] The difference from Example 1 is:

[0144] In step (4):

[0145] 10.2 g of solution B (polyvinyl alcohol solution) and 10.6 g of solution C (tannic acid solution) were added to solution A in step (1), and stirred at room temperature for 1 h to obtain solution D.

[0146] The remaining steps are the same as those in Example 1 to obtain a PEDOT:PSS flexible conductive film.

[0147] Comparative Example 2

[0148] The difference from Example 2 is:

[0149] In step (4):

[0150] 10.2 g of solution B (polyvinyl alcohol solution) and 11.2 g of solution C (tannic acid solution) were added to solution A in step (1), and stirred at room temperature for 1 h to obtain solution D.

[0151] The remaining steps are the same as those in Example 2 to obtain a PEDOT:PSS flexible conductive film.

[0152] Comparative Example 3

[0153] The difference from Example 1 is:

[0154] In step (1):

[0155] Solution A is 10 g PEDOT:PSS aqueous solution (Clevios PH 1000);

[0156] In step (3):

[0157] Only deionized water in the same amount as in Example 1 was contained as Solution C.

[0158] The remaining steps are the same as those in Example 1 to obtain a PEDOT:PSS flexible conductive film.

[0159] Comparative Example 4

[0160] The difference from Example 1 is:

[0161] In step (3):

[0162] Only deionized water in the same amount as in Example 1 was contained as Solution C.

[0163] The remaining steps are the same as those in Example 1 to obtain a PEDOT:PSS flexible conductive film.

[0164] Comparative Example 5

[0165] The difference from Example 1 is:

[0166] In step (1):

[0167] Solution A is 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000).

[0168] The remaining steps are the same as those in Example 1 to obtain a PEDOT:PSS flexible conductive film.

[0169] Comparative Example 6

[0170] The difference from Example 2 is:

[0171] In step (1):

[0172] Solution A is 10 g of PEDOT:PSS aqueous solution (Clevios PH 1000).

[0173] The remaining steps are the same as those in Example 2 to obtain a PEDOT:PSS flexible conductive film.

[0174] Comparative Example 7

[0175] This comparative example provides an electrode, and the preparation method is as follows:

[0176] (1) adding dimethyl sulfoxide, PEDOT:PSS aqueous solution, polyvinyl alcohol, xanthan gum and surfactant (Fs-31) into a glass bottle, stirring the solution at 80° C. for 4 h to prepare a precursor solution;

[0177] (2) Add tannic acid to the precursor solution and stir for 5 minutes to obtain a solution for preparing an electrode. The contents of the components are as follows:

[0178] PEDOT:PSS 0.4wt%, polyvinyl alcohol 0.8wt%, tannic acid 6.4wt%, xanthan gum 0.4wt%, surfactant 0.1wt%, dimethyl sulfoxide 5vol%;

[0179] (3) The solution was then dropped onto the substrate and dried in an oven at 80°C to obtain an electrode film.

[0180] The electrical properties of the PEDOT:PSS flexible conductive films prepared in Examples 1 to 14 and Comparative Examples 1 to 7 were tested using a four-probe resistance tester with a test strip length of 20 mm and a strip width of 15 mm. The results are shown in Table 1.

[0181] Elongation at break test: A universal tensile testing machine was used for the test, the test temperature was 22°C, and the tensile speed was set to 5 mm / min. The spline was cut into a dumbbell shape, the effective length for stretching was 20 mm, and the spline width was 4 mm. The results are shown in Table 1.

[0182] Table 1 Electrical and mechanical properties of PEDOT:PSS flexible conductive films

[0183]

[0184] As can be seen from Table 1, by comparing Examples 1 to 3, it can be seen that the tannic acid content increases, the elongation at break increases, the tensile properties of the film are improved, but the conductivity decreases slightly. It can be seen from Comparative Examples 1 to 2 and Examples 1 to 2 that when glycerol is added as a humectant, the elongation at break of the film is greatly improved, which can greatly improve the tensile properties of the film, and the tensile properties can be maintained for more than 28 days. In actual situations, the composition of the raw materials can be adjusted within an appropriate range according to actual needs to obtain a flexible conductive film with suitable performance. However, the flexible conductive film of Comparative Examples 1 to 2 does not contain glycerol. After being placed at room temperature for 14 days, the film becomes hard and brittle, has no flexibility, and the spline breaks during the cutting process. It is impossible to obtain a complete spline, and it is impossible to perform a mechanical property test, and thus the elongation at break data cannot be obtained. The electrode film of Comparative Example 7 does not contain glycerol. After the film is placed for 14 days, the elongation at break drops sharply, loses tensile properties and adhesion, and has poor stability. It can be seen from Comparative Examples 3 to 6 that ethylene glycol can improve the conductivity, and both ethylene glycol and tannic acid have a certain degree of influence on the tensile properties of the conductive film.

[0185] The adhesion of the PEDOT:PSS flexible conductive films prepared in Examples 1 to 14 and Comparative Examples 1 to 7 was tested: the adhesion of the film on the glass sheet was tested by interfacial adhesion according to the standard 90-degree peel test method, with a peeling speed of 0.5 mm / s, a strip length of 25 mm, and a width of 10 mm. The results are shown in Table 2.

[0186] Table 2 Adhesion data of PEDOT:PSS flexible conductive film

[0187]

[0188]

[0189] As can be seen from Table 2, by comparing Example 1 to Example 3, it is shown that as the tannic acid content increases, the adhesion of the conductive film increases.

[0190] Compared with Comparative Examples 1-2, glycerol is added to the conductive film of Examples 1-2, and as the drying time increases, the adhesion gradually increases and then decreases. The conductive film in Examples 1-2 still has adhesion after drying at 60°C for 20 hours, indicating that the addition of glycerol can improve the stability of the conductive film, including stretchability and adhesion, which is very beneficial for the storage of the conductive film or use in extreme cases. In Comparative Examples 3-6, tannic acid and ethylene glycol are not contained at the same time, and the adhesion is weak or even non-sticky. Ethylene glycol has certain surfactant properties, and the system containing ethylene glycol has a more uniform film formation and the conductive film has better adhesion. The electrode film in Comparative Example 7 does not contain glycerol and loses adhesion after drying for a period of time.

[0191] The myoelectric signal conduction performance of the PEDOT:PSS flexible conductive film (as a flexible electrode) prepared in step (5) of Examples 1 to 2 and Comparative Examples 1 to 7 was tested, and the specific testing method is as follows:

[0192] Two working electrodes (flexible electrodes) were attached to the inner side of the subject's forearm with a spacing of 2 cm, the reference electrode (flexible electrode) was connected to the outer bone protrusion of the elbow, and the three electrodes were connected to the electromyographic signal acquisition device (EMG muscle electrical sensor 3IT_EMGC1V1) to record the electromyographic signal of the subject's hand movement. In the comparative example with weaker viscosity, the test was performed after fixing the electrodes with medical tape.

[0193] Test results such as Figure 1 shown. Figure 1 The graph is a test result of the electromyographic signal transmission performance of the PEDOT:PSS flexible conductive film prepared in Examples 1 to 2 of the present invention and Comparative Examples 1 to 7 as a flexible electrode. Figure 1 It can be seen that the signals measured by the flexible electrodes of Examples 1 and 2 are very stable, with a stable baseline and a sufficiently high signal-to-noise ratio, which is sufficient for subsequent signal analysis. Among them, Example 2 has the smallest baseline peak-to-peak noise and the largest peak-to-peak amplitude during hand movement.

[0194] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A flexible conductive film obtained by drying a solution comprising PEDOT:PSS, a water-soluble polymer, a viscosity aid, a humectant and a polar solvent; In the solution, the mass content of PEDOT:PSS is 0.1% to 1%, the mass content of water-soluble polymer is 0.2% to 3%, the mass content of viscosity auxiliary agent is 0.5% to 10%, the mass content of moisturizing agent is 1% to 10%, and the mass content of polar solvent is 1% to 8%.

2. The flexible conductive film according to claim 1, characterized in that: The water-soluble polymer includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylamide and polyethylene glycol; the viscosity auxiliary agent includes at least one of tannic acid, dopamine, tea polyphenols, catechins, anthocyanins and proanthocyanidins; the moisturizer includes at least one of glycerin, propylene glycol, butylene glycol, hyaluronic acid, trehalose, squalane, hyaluronic acid, octadecyl alcohol, sorbitol, urea and D-panthenol; the polar solvent includes at least one of ethylene glycol and dimethyl sulfoxide.

3. The flexible conductive film according to claim 1, characterized in that: The thickness of the flexible conductive film is 20-200 μm.

4. The method for preparing the flexible conductive film according to any one of claims 1 to 3, comprising the following steps: A PEDOT:PSS aqueous solution, a water-soluble polymer, a viscosity aid, a humectant, a polar solvent and water are mixed, and the obtained solution is dried to obtain a flexible conductive film.

5. The preparation method according to claim 4, characterized in that: The method for preparing the flexible conductive film comprises the following steps: S1) stirring and mixing solution A, solution B, solution C and a moisturizer to obtain solution D; The solution A is obtained by mixing a PEDOT:PSS aqueous solution and a polar solvent; The solution B is obtained by dissolving a water-soluble polymer in water; The solution C is obtained by dissolving a viscosity aid in water; S2) adding the solution D dropwise onto the substrate, and after drying, obtaining a flexible conductive film.

6. The preparation method according to claim 5, characterized in that: The mixing of the PEDOT:PSS aqueous solution and the polar solvent is carried out at room temperature; the mixing is carried out by stirring.

7. The preparation method according to claim 5, characterized in that: The solution B is obtained by mixing a water-soluble polymer and water, and then heating and stirring until the water-soluble polymer is completely dissolved in the water; the heating and stirring temperature is 75-85° C.; and the mass concentration of the solution B is 2.2%-10%.

8. The preparation method according to claim 5, characterized in that: The solution C is obtained by mixing a viscosity aid and water and stirring until the viscosity aid is completely dissolved in the water; the stirring temperature is room temperature; and the mass concentration of the solution C is 2% to 16.7%.

9. Use of the flexible conductive film according to any one of claims 1 to 3, or the flexible conductive film prepared by the preparation method according to any one of claims 4 to 8 in flexible electronic devices.

10. A flexible electronic device, comprising the flexible conductive film according to any one of claims 1 to 3, or the flexible conductive film prepared by the preparation method according to any one of claims 4 to 8.

Citation Information

Patent Citations

  • High-conductivity stretchable PEDOT: PSS film and preparation method and application thereof

    CN115785499A

  • Patternable flexible electrode film and preparation method and application thereof

    CN116612932A